A retrospective study of ultrasound-guided high intensity focussed ultrasound ablation for multiple uterine fibroids in South Africa. (17th November 2018) - He, Min; Jacobson, Hayley; Zhang, Cai; Setzen, Raymond; Zhang, Lian
Abstract: Objective: To evaluate the shrinkage rate, symptom relief and improvement of the quality of life following ultrasound-guided high intensity focussed ultrasound (USgHIFU) for multiple uterine fibroids. Methods: From October 2015 to November 2016, 81 black women with multiple symptomatic fibroids underwent USgHIFU. The number of the fibroids ranged from 3 to 9. The shrinkage rate of fibroids, symptom severity score and quality of life were evaluated following USgHIFU. Magnetic resonance imaging (MRI), the uterine fibroid symptom and quality of life (UFS-QOL) questionnaire were used for evaluation. Results: The mean age of patients was 35.3 ± 5.9 years. The average weight of these patients was 68.4 ± 11.4 kg, with the median abdominal subcutaneous fat thickness of 38.0 ± 11.4 mm. The median fibroid volume was 36.0 (range: 1.8–1220.1) cm³. During HIFU, 60.5% of the patients reported lower abdominal pain, 43.2% sciatic/buttock pain, 60.5% skin "burning" sensation, 6.2% abnormal vaginal discharge and 13.6% transient leg pain. No severe complications were observed. The average volume reduction rate of fibroids in 21 patients who completed the follow-up was 32.5 ± 24.0, 42.3 ± 32.2 and 52.5 ± 36.3% 1, 3 and 6 months after HIFU, respectively. The UFS score decreased and the QOL values significantly increased during the follow-up period. Re-intervention treatment occurred in two of the 21 patients 6 months after HIFU. One patient conceived 3 months after HIFU, and she had a term vaginal delivery without any obstetrical complications. Conclusions: Based on our results, USgHIFU is safe and effective in treating patients with multiple uterine fibroids.